Religious Tolerance Messages on Social Media: Insights from Deddy Corbuzier's 'Log in' Program - Muh Ali Bagas; Heriyadi; Firyal, Wafda (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2024)
The rise of social media has intensified challenges related to misinformation and interfaith conflicts, underscoring the critical need for platforms promoting religious tolerance. This study investigates the